Construction de la fiabilité organisationnelle en environnement extrême à partir de la sécurité réglée et gérée : étude de cas du raid Concordia - Aude Villemain; Patrice Godon (Perspectives Interdisciplinaires sur le Travail et la Santé)
This explorative study attempts to understand how regulated and managed safety was constructed during traverses on the Antarctic continent in order to ensure organizational reliability. Risk situations were ranked based on participants’ observations, marks left by the activity, and interviews with the project manager. The first results showed that safety was ensured by: (a) a traverse design involving duplicated survival systems, (b) an organisation requiring the succession and synchronisation of tasks, and (c) the development of new know-how regarding safety and the various professions involved. The discussion of the results focuses on the room for manoeuvre induced by the organisation of the traverse and the equipment design, all of which enabled the operators to be self-sufficient, which is a fundamental necessity in developing overall safety.